2015
DOI: 10.1371/journal.pone.0123133
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling (SOCS) Genes Are Silenced by DNA Hypermethylation and Histone Deacetylation and Regulate Response to Radiotherapy in Cervical Cancer Cells

Abstract: Suppressor of cytokine signaling (SOCS) family is an important negative regulator of cytokine signaling and deregulation of SOCS has been involved in many types of cancer. All cervical cancer cell lines tested showed lower expression of SOCS1, SOCS3, and SOCS5 than normal tissue or cell lines. The immunohistochemistry result for SOCS proteins in human cervical tissue also confirmed that normal tissue expressed higher level of SOCS proteins than neighboring tumor. Similar to the regulation of SOCS in other type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Although mutations in the SOCS family genes are very rare, aberrant SOCS signaling has been linked to the epigenetic deregulation of their expression . For instance, reduced levels of SOCS5 mRNA and its promoter hypermethylation were reported in hepatocellular carcinoma, cervical cancer, and thyroid tumors . In this study, we dissected the mechanism of epigenetic deregulation of SOCS5 expression in T‐ALL through aberrant DNA methylation.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although mutations in the SOCS family genes are very rare, aberrant SOCS signaling has been linked to the epigenetic deregulation of their expression . For instance, reduced levels of SOCS5 mRNA and its promoter hypermethylation were reported in hepatocellular carcinoma, cervical cancer, and thyroid tumors . In this study, we dissected the mechanism of epigenetic deregulation of SOCS5 expression in T‐ALL through aberrant DNA methylation.…”
Section: Discussionmentioning
confidence: 97%
“…DNMT3A was identified to negatively regulate the SOCS5 expression levels in T‐ALL cells. Histone acetylation has also been implicated in the epigenetic regulation of the SOCS family genes in solid tumors . In addition, early studies identified the CpG binding protein, MeCP2 as a transcriptional silencer .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations